PENGARUH GAYA MENGAJAR TEKNOLOGIS GURU PENDIDIKAN AGAMA KRISTEN TERHADAP GAYA BELAJAR VISUAL SISWA KELAS VIII SMP N 1 PAHAE JULU K KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2018/2019” - martha simorangkir (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
vAbstract, The research aims to know of percentage the teknological teaching style of teachers christianeducation towards students visual learning styles in class VIII SMP Negeri 1 Pahae Julu Tapanuli Utararegency in 2018/2019 academic years. The hypothesis of this research was: there is a positive and significantinfluence teknological teaching style of teachers christian education towards students visual learning styles inclass VIII SMP Negeri 1 Pahae Julu Tapanuli Utara in 2018/2019 academic years.Research instrument in the form of a closed questionnaire prepared by the research. analyzing datawas indicated that the teknological teaching style of teachers christian education towards students visuallearning styles in class VIII SMP Negeri 1 Pahae Julu Tapanuli Utara by 16,40 % with the calculation bycomparing tcount ttable namely 2,426 2,042. Tes the regression equation between X and Y with.Hypothesis test indicated that the Fcount Ftable namely 5,870 1,62 then H0 rejected and Haaccepted. the conclusion drawn from this study was there is a positive and significant influence teknologicalteaching style of teachers christian education towards students visual learning styles in class VIII SMP Negeri 1Pahae Julu Tapanuli Utara regency in 2018/2019 academic years.Keywords : teknological teaching style of teachers christian education, students visual learning styles.